PENINGKATAN KESIAPSIAGAAN BENCANA EMISI UDARA PADA KELOMPOK MAJLIS TA’LIM BAITURRAHMAN PESONA BANYU ASRI MELALUI IMPLEMENTASI MANAJEMEN UDARA BERBASIS IOT - Budianto, Arif; Alaydrus, Alfina Taurida; Akhyar, Halil; Rahayu, Susi; Hasanah, Khofizzatul; Nurfadilah, Nurfadilah; Andini, Mira; Pranahita, Dewa Dwi; Wardi, Palaivia Harman (Universitas Mataram, 2025)
Air emissions are a critical issue that can directly impact public health. The larger the emission source, the greater the potential for exposure to the resulting emissions. This problem is also faced by residents (partners) in the Pesona Banyu Asri neighborhood, Banyumulek, West Lombok Regency. Air pollution generated from many directions (four main sources) in the partner area (waste management at the Kebon Kongok landfill, plastic waste processing at BRIDA, waste processing into biofuel, and the pottery production process in the Banyumulek tourist village) is quite high, but the process of quantifying and characterizing emissions has not been implemented/studied in detail. Therefore, the purpose of this community service is to provide alternative solutions that can improve community preparedness regarding air emission disaster mitigation. The implementation method of community service activities is focused on PAR (participatory action research) techniques to improve social aspects of the community. The priority is to identify problems and provide alternative solutions related to the impact of air emission exposure due to emission source activities around the partner area. The IoT (Internet of Things)-based air management system developed by the community service team was previously implemented directly in the community, through stages of observation, socialization, training, installation, and final assessment. The results of the community service process can be seen from the questionnaire data quantification process, where there was a significant increase between before and after the community service activity. The readiness of the partner community increased by 62% regarding the ability to understand air mitigation, both in terms of understanding the types of air emissions, air purification systems, and the operation of the IoT-based air management system that is beneficial for partners.